2016
DOI: 10.1097/md.0000000000002272
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Assessment of the AJCC Tumor Regression Grading System After Preoperative Chemoradiotherapy for Chinese Locally Advanced Rectal Cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
2
19
0
1
Order By: Relevance
“…Meanwhile, CA 19-9 is another widely used tumor marker in gastrointestinal tumor and is a significant predictor of survival for rectal cancer 3032. However, few studies analyzed the association between CA19-9 and nCRT response.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, CA 19-9 is another widely used tumor marker in gastrointestinal tumor and is a significant predictor of survival for rectal cancer 3032. However, few studies analyzed the association between CA19-9 and nCRT response.…”
Section: Discussionmentioning
confidence: 99%
“…TRG is a type of grading metric used in the histological stratification of tumor response after chemoradiotherapy, and it was first used in the evaluation of the efficacy of concurrent chemoradiotherapy in esophageal, gastric, bladder, and head and neck cancers. 13 17 Later, studies reported that TRG had a significant correlation with the prognosis of LARC, 6 10 and it was gradually used to evaluate the progression of rectal cancer. There are mainly 6 types of TRG systems at present, which divide the TRG into 3–5 grades, but no unified standards have yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the tumor regression grade (TRG) had significant correlation with the prognosis of LARC 6 10 and is gradually being used to assess the progression of rectal cancer. Thus far, mainly six types of TRG systems have been used, and the American Joint Committee on Cancer (AJCC)-TRG has been found to be better than any other system as it can be more accurate in predicting the occurrence of distant metastasis (DM) due to rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A blood sample of patients was collected after each cycle of chemotherapy. Carbohydrate antigen 19-9 and serum carcinoembryonic antigen in blood samples were evaluated by a pathologist who was blind to the chemotherapeutic treatments [ 20 ].…”
Section: Methodsmentioning
confidence: 99%